PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII5 SMP NEGERI 1 UJUNGBATU - Agnesy, Abnur Melsyah Agnesy Melsyah; Dian, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to improve learning process and mathematics learning outcomes in SMP Negeri 1 Ujungbatu by implementing cooperative learning model type Talking Stick to mathematics lesson. Subjects of the research were students grade VII5 who have the academic ability of the heterogeneous. This research is a classroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score, the result of study in the first cycle found that the percentage of students who achieve KKM is 68,44% and the second cycle is 80,55%, an increase from before the measures the percentage is only 52,77%. Results of this research indicate that the implementing of cooperative learning model type Talking Stick can improve learning process and the mathematics learning outcomes of students grade VII5 SMP Negeri 1 Ujungbatu in the second semester academic year 2013/2014. Key words: Learning process, Mathematics learning outcome, Cooperative learning, Talking Stick, Classroom action research.